Impact of the COVID-19 pandemic on prehospital emergency medical service: a scoping review - Richter, Hannah; Schneider, Marlieke; Eisenberger, Johanna; Jafari, Nastaran; Haumann, Hannah; Häske, David (Frontiers in Public Health, 2025)
BackgroundThe COVID-19 pandemic has had an unprecedented impact on healthcare systems worldwide. Emergency medical services (EMS) frequently served as the sole point of contact for individuals in need of assistance or emergency support. This study aimed to map the impact of the pandemic on emergency calls and EMS operations.MethodsA systematic literature search was conducted in the electronic databases Pubmed and Web of Science. A hand search supplemented the search. Published articles in English or German dealing with frequencies, diagnoses, and factors influencing emergency calls and EMS use were included. Studies on cardio-pulmonary resuscitation were not included.ResultsThe initial search yielded 3,359 articles, of which 3,187 were screened by title/abstracts, and 120 full-text articles were analyzed. Fifty articles were then included. Fourteen articles reported the number of emergency calls, 30 on the number of EMS operations, and six on both outcomes. The articles were mostly published in 2020 (n = 18) or 2021 (n = 29) and dealt with the situation of EMS during the COVID-19 pandemic in 13 European countries and 11 non-European countries. However, the quantitative data on changes in emergency calls show considerable variation (standard deviation of 31.3% with a mean of 0.0%, minimum: −50.0% to maximum: 121.0%). The quantitative data on changes in EMS operations show a more significant overall decrease (mean: −12.2%, standard deviation: 24.7%, minimum: −72% to maximum: 56%).ConclusionsThe heterogeneity of the studies is considerable; overall, there appears to have been a decline in emergency calls, particularly EMS operations. Clear patterns, e.g., by region, cannot be identified.Review protocol registrationThe review protocol is registered in the Open Science Framework: https://osf.io/8urq9.